Carissa grandiflora Natal Plum, Common Carissa - Edward Gilman (EDIS, 2007)
This document provides a detailed overview of the Carissa grandiflora, commonly known as the natal plum. It describes the plant’s physical characteristics, including its evergreen nature, lustrous green leaves, white star-shaped flowers, and bright red, edible fruit. The document highlights the plant’s adaptability to various soil types and light conditions, its high drought tolerance, and its suitability for use in hedges, screens, and ground covers. Additionally, it notes the plant’s moderate growth rate, dense habit, and minimal pest issues, while cautioning against overwatering to prevent root rot. Original publication date October 1999.